2017
DOI: 10.3390/s17092038
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Optical Signal Multipath

Abstract: Here, we propose a model to determine the effect of multipath in indoor environments when the shape and characteristics of the environment are known. The main paper goal is to model the multipath signal formation to solve, as much as possible, the negative effects in light communications, as well as the indoor positioning errors due to this phenomenon when using optical signals. The methodology followed was: analyze the multipath phenomenon, establish a theoretical approach and propose different models to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The optical signal reflection model reported in [25] allows modeling how the multipath affects the measurement techniques based on AoA and PoA. In [26], a procedure was proposed to measure the signal value that impacts into the PSD (detector) surface as a result of MP. In [27], position errors due to MP were characterized by working with AoA and PoA techniques, to complement the previous works.…”
Section: Introductionmentioning
confidence: 99%
“…The optical signal reflection model reported in [25] allows modeling how the multipath affects the measurement techniques based on AoA and PoA. In [26], a procedure was proposed to measure the signal value that impacts into the PSD (detector) surface as a result of MP. In [27], position errors due to MP were characterized by working with AoA and PoA techniques, to complement the previous works.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth analysis is out of the scope of our paper (the MP effect will be studied in future works). However, in our related work [ 33 ], we have verified the effect of MP in our system and the result was that the fact of having obstacles that generate MP has a very little effect on the determination of the impact point with this technique. Note that the RSS received at each electrode of the PSD sensor is a subtractive composition of currents, which partially compensates the MP and their effect in the location determination.…”
Section: Resultsmentioning
confidence: 57%
“…The latter, however, is a critical source of inaccuracy in optical IPSs. When the environment remains unchanged, partial compensation could be introduced by applying the model presented in [ 27 ] after characterization of the geometry and material composition of the environment. This, however, would require significant effort; multipath errors are therefore likely to remain the dominant source of error in most real applications.…”
Section: Discussionmentioning
confidence: 99%
“…A complete analysis and correction of these distortions was presented in [ 24 , 25 ]. A procedure to model and correct the errors due to multipath effects was proposed in [ 26 , 27 , 28 ]. From those previous works, it can be concluded that PSD-based IPSs using AoA observations provide better positioning performance than implementations using phase differences.…”
Section: Introductionmentioning
confidence: 99%